Caracterização endoscópica de pacientes pediátricos de acordo com o novo sistema de graduação e classificação endoscópica da esofagite eosinofílica - Marson, Luciane Borges (2017)
Background: The EREFS has been used for diagnosis assessment and prediction of the activity and remission of the disease in EoE adult patients. However, there are a few studies in which the effectiveness of this endoscopic metric has been tested in children. Aim: To characterize the EREFS features in a pediatric population who underwent diagnostic endoscopy, and to assess the score utility for EoE diagnosis. Methods: Pediatric endoscopic prospective cohort conducted in a Brazilian population, evaluating patients with gastrointestinal complaints without definitive diagnosis. The demographic and clinical data were evaluated. After the endoscopic procedure the original EREFS was scored, unware of the final diagnosis of EoE, GERD or Control. Results: One hundred and seven patients undergoing endoscopies were included. The inflammatory features were more frequently scored than fibrostenotic. The T-EREFS showed the sensitivity of 75%, specificity of 85.7%, accuracy of 84.1%, and AUC was 0.80. The medians of T-EREFS were 2.5, 0.5, and 0.0 for EoE, GERD, and Controls, respectively. There was a significant statistic difference between EoE T-EREFS x Control T-EREFS (p<0.0001) and EoE T-EREFS x GERD T-EREFS (p=0.0375). Conclusion: The data suggest that T-EREFS is a useful diagnostic tool for pediatric EoE with acceptable sensitivity, good specificity, and accuracy. The inflammatory features are more frequently found than fibrostenotic features in the assessment of pediatric endoscopic EoE diagnosis. Some features present in the original EREFS may be likely suppressed for the diagnostic EoE pediatric analysis, as in the modified EREFS used in adults.